The effectiveness of learning mind maps on Matrix Operations in SMK Darur Rahmah - Darsan, Darsan; Muis, Abdul; Priawasana, Endra (International Journal of Trends in Mathematics Education Research, 2023)
A mind map is a note-taking method that involves laying out ideas on a sheet of paper and branching out along the lines of one's thought processes. With mind mapping, learning will be easy to describe, and material that is quite difficult can be easily understood or simplified. This study aims to describe the effectiveness of mind mapping learning in matrix operations material in grade 11. Three indicators of learning effectiveness are: 1) teacher management of learning; 2) student involvement in learning activities; and 3) the proportion of students who successfully complete learning objectives. This study uses observation, tests, interviews, and documentation to collect data for a qualitative descriptive analysis. Class XIA SMK students Darur Rahmah was used as the research sample. Based on the findings and discussion of the research, class XIA SMK Darur Rahmah studied matrix operation material effectively using activities in mind mapping. The results showed that three indicators were fulfilled: 1) effectiveness, namely the teacher's ability to determine the very good category; 2) 11 students whose activities were classified as active; 16 students were very active; and 3) individual completeness of 25 students with a learning completeness level of 92.6%.